Implementasi Sistem Peringatan Banjir Dini dengan Sensor HC-SR04 Berbasis ESP32 Internet of Things - Sujono Sujono; Muhammad Rusli M (Computer Journal, 2026)
Floods are natural disasters that often occur in Indonesia and sometimes cause great material and human losses. This paper describes the design and implementation of an IoT-based flood early warning system using ESP32 microcontroller and HC-SR04 ultrasonic sensor technology. The system is capable of automated river water level measurements at 5 minutes interval with real-time data sent to a web-based monitoring dashboard. Field validation was conducted in a quantitative experimental study at a river dam facility located in Jombang Regency. Performance testing results show that the system has high reliability, achieving 98.63% data transmission success rate. The HC-SR04 sensor has measurement accuracy of 97.69% with Mean Absolute Error (MAE) value equal to 2.31%. The warning mechanism works by comparing the water level with certain thresholds so that the dashboard can display safe or alert status conditions based on measurements made by the HC-SR04 sensor. Experimental results prove that this system is effective and economically feasible as a flood early warning solution for vulnerable regions, enhancing disaster preparedness capabilities significantly.